Dietary supplementation with fructooligosaccharides ameliorates allergy development following DEHP exposure in mice. Issue 1 (1st January 2021) - Yasuda, Akiko; Inoue, Ken-ichiro; Sanbongi, Chiaki; Suzuki, Wakako; Takano, Hirohisa
ABSTRACT: Fructooligosaccharides (FOS), a prebiotic supplement, can enhance immunological responses, probably through regulation of gastrointestinal microflora. On the other hand, some environmental pollutants have adjuvanticity against allergic reactions/diseases. The purpose of this study was to evaluate the effects of dietary supplementation with FOS on a murine model of enhanced ovalbumin (OVA)-related allergic peritonitis induced by di-(2-ethylhexyl) phthalate (DEHP). C3H/HeN mice were intraperitoneally administered OVA and DEHP, and fed a diet containing 2.5% FOS. Thereafter, several parameters were evaluated. Supplementation with FOS alleviated OVA plus DEHP-related peritoneal inflammation characterized by infiltration of polymorphonuclear leukocytes including neutrophils in the peritoneal cavity. Also, FOS administration declined the number of mast cells of OVA + DEHP treated mice. FOS suppressed the elevated protein level of interleukin-5, eotaxin, and keratinocyte-derived chemoattractant, in the peritoneal lavage fluids. Our results suggest that dietary supplementation with FOS can prevent or ameliorate enhanced allergic peritoneal inflammation induced by DEHP.